Edukasi Penguasaan Ilmu Tahsinul Qur’an untuk Meningkatkan Bacaan Al-Qur’an Santri Taman Pendidikan Al-Qur’an Ar Royyan Pacitan - Adhi Kuncoro; Sanjaka Yekti (Pusat riset dan Inovasi Nasional, 2026)
Background: The Quran is a guide for Muslims, so the ability to read the Quran correctly according to the rules of tajweed (tahsin) is a crucial basic competency. At the Ar Royyan Pacitan Quranic Education Center (TPQ), several students still have weaknesses in the pronunciation of the letters and the accuracy of the length of the recitation (mad). Objective: This community service activity aims to educate and improve the students' mastery of tahsin in order to achieve a quality Quran recitation that meets the standards of tajweed. Method: The talaqqi and musyafahah methods are used, in which students listen directly to examples of recitation from the teacher and then practice them repeatedly. The stages of the activity include a placement test, the provision of practical theoretical material, and intensive recitation guidance (setoran). Results: The educational results show a significant increase in the fluency of letter pronunciation (makharijul huruf) and the accuracy of basic tajweed rules among the students. Furthermore, students' motivation to learn increased along with their understanding of the importance of reading the Quran with tartil. Conclusion: Tahsin education through interactive and intensive methods has proven effective in improving the reading quality of students at TPQ Ar Royyan. Ongoing mentoring is recommended to maintain and develop these skills.